TINJAUAN YURIDIS MENGENAI TANGGUNG JAWAB PELAKU TINDAK PIDANA PENCURIAN: ANALISIS BERDASARKAN PASAL 362 KITAB UNDANG-UNDANG HUKUM PIDANA (KUHP) - Pane, Musa Darwin; Endang Renika Siahaan, Genesistha (Universitas Stikubank, 2025)
The use of criminal law in crime prevention efforts tends to only function as a treatment step for symptoms that appear, not as a tool that is able to eliminate the root causes of crime itself. Criminal law focuses on imposing sanctions on perpetrators as a form of retribution and special prevention, but often does not touch on the underlying factors that drive a person to commit a crime, such as economic conditions, social environment, and education. One of the most frequent forms of crime in society is theft, which reflects the existence of structural problems that have not been fully resolved This research uses a descriptive method of analysis. Where the analysis is carried out in accordance with the provisions of the rule of law with a conceptual approach, which refers to the provisions of the law and other legal disciplines. The type of approach in this research is carried out through normative juridical means. By doing legal interpretation associated with legislation, it also examines and tests secondary data, namely primary legal material in the form of the Criminal Code Article 362 concerning Theft, secondary legal material in the form of doctrine or expert opinion, and tertiary legal material in the form of papers, articles and others, The conclusion of this research is that theft is a criminal offense in the Criminal Code which is classified based on the method, place and conditions of its implementation. Article 362 of the Criminal Code defines theft as the act of taking property belonging to another person unlawfully for possession. In addition, there are other types of theft, such as theft with aggravation (Article 363), theft with violence (Article 365), petty theft (Article 364), and theft in the family (Article 367), each with different sanctions. Keywords : Responsibility, theft, Criminal Code.